If a and b are rational numbers, find a and b,
* √2+√3/3√2-2√3= a+b√6
* 5+2√3/7+4√3= a+b√3
Answers
Answered by
2
Answer is attached below
Hope it helps
Hope it helps
Attachments:
![](https://hi-static.z-dn.net/files/d0b/e420b67caa67db75d0b1ee141d0cee8f.jpg)
![](https://hi-static.z-dn.net/files/dae/a36a1c15b9704e6be998ec1d70815ced.jpg)
Answered by
4
Hey friend,
Here is the answer you were looking for:
![1) \\ \frac{ \sqrt{2} + \sqrt{3} }{3 \sqrt{2} - 2 \sqrt{3} } = a + b \sqrt{6} \\ \\ on \: rationalizing \: the \: denominator \: we \: get \\ \\ = \frac{ \sqrt{2} + \sqrt{3} }{3 \sqrt{2} - 2 \sqrt{3} } \times \frac{3 \sqrt{2} + 2 \sqrt{3} }{3 \sqrt{2} + 2 \sqrt{3} } \\ \\ using \: the \: identity \\ (a + b)(a - b) = {a}^{2} - {b}^{2} \\ \\ = \frac{ \sqrt{2} \times 3 \sqrt{2} + \sqrt{2} \times 2 \sqrt{3} + \sqrt{3} \times 3 \sqrt{2} + \sqrt{3} \times 2 \sqrt{3} }{ {(3 \sqrt{2}) }^{2} - {(2 \sqrt{3}) }^{2} } \\ \\ = \frac{3 \times 2 + 2 \sqrt{6} + 3 \sqrt{6} + 2 \times 3}{18 - 12} \\ \\ = \frac{6 + 5 \sqrt{6} + 6}{6} \\ \\ \frac{12 + 5 \sqrt{6} }{6} = a + b \sqrt{6} \\ \\ a = \frac{12}{6} \\ \\ a = 2 \\ \\ b = \frac{5}{6} \\ \\ 2) \\ \frac{5 + 2 \sqrt{3} }{7 + 4 \sqrt{3} } = a + b \sqrt{3} \\ \\ on \: rationalizing \: the \: denominator \: we \: get \\ \\ = \frac{5 + 2 \sqrt{3} }{7 + 4 \sqrt{3} } \times \frac{7 - 4 \sqrt{3} }{7 - 4 \sqrt{3} } \\ \\ using \: the \: identity \\ (a + b)(a - b) = {a}^{2} - {b}^{2} \\ \\ = \frac{5 \times 7 - 5 \times 4 \sqrt{3} + 2 \sqrt{3} \times 7 - 2 \sqrt{3} \times 4 \sqrt{3} }{ {(7)}^{2} - {(4 \sqrt{3} )}^{2} } \\ \\ = \frac{35 - 20 \sqrt{3} + 14 \sqrt{3} - 8 \times 3}{49 - 48} \\ \\ = 35 - 24 - 20 \sqrt{3} + 14 \sqrt{3} \\ \\ 11 - 6 \sqrt{3} = a + b \sqrt{3} \\ \\ a = 11 \\ \\ b = - 6 1) \\ \frac{ \sqrt{2} + \sqrt{3} }{3 \sqrt{2} - 2 \sqrt{3} } = a + b \sqrt{6} \\ \\ on \: rationalizing \: the \: denominator \: we \: get \\ \\ = \frac{ \sqrt{2} + \sqrt{3} }{3 \sqrt{2} - 2 \sqrt{3} } \times \frac{3 \sqrt{2} + 2 \sqrt{3} }{3 \sqrt{2} + 2 \sqrt{3} } \\ \\ using \: the \: identity \\ (a + b)(a - b) = {a}^{2} - {b}^{2} \\ \\ = \frac{ \sqrt{2} \times 3 \sqrt{2} + \sqrt{2} \times 2 \sqrt{3} + \sqrt{3} \times 3 \sqrt{2} + \sqrt{3} \times 2 \sqrt{3} }{ {(3 \sqrt{2}) }^{2} - {(2 \sqrt{3}) }^{2} } \\ \\ = \frac{3 \times 2 + 2 \sqrt{6} + 3 \sqrt{6} + 2 \times 3}{18 - 12} \\ \\ = \frac{6 + 5 \sqrt{6} + 6}{6} \\ \\ \frac{12 + 5 \sqrt{6} }{6} = a + b \sqrt{6} \\ \\ a = \frac{12}{6} \\ \\ a = 2 \\ \\ b = \frac{5}{6} \\ \\ 2) \\ \frac{5 + 2 \sqrt{3} }{7 + 4 \sqrt{3} } = a + b \sqrt{3} \\ \\ on \: rationalizing \: the \: denominator \: we \: get \\ \\ = \frac{5 + 2 \sqrt{3} }{7 + 4 \sqrt{3} } \times \frac{7 - 4 \sqrt{3} }{7 - 4 \sqrt{3} } \\ \\ using \: the \: identity \\ (a + b)(a - b) = {a}^{2} - {b}^{2} \\ \\ = \frac{5 \times 7 - 5 \times 4 \sqrt{3} + 2 \sqrt{3} \times 7 - 2 \sqrt{3} \times 4 \sqrt{3} }{ {(7)}^{2} - {(4 \sqrt{3} )}^{2} } \\ \\ = \frac{35 - 20 \sqrt{3} + 14 \sqrt{3} - 8 \times 3}{49 - 48} \\ \\ = 35 - 24 - 20 \sqrt{3} + 14 \sqrt{3} \\ \\ 11 - 6 \sqrt{3} = a + b \sqrt{3} \\ \\ a = 11 \\ \\ b = - 6](https://tex.z-dn.net/?f=1%29+%5C%5C++%5Cfrac%7B+%5Csqrt%7B2%7D++%2B++%5Csqrt%7B3%7D+%7D%7B3+%5Csqrt%7B2%7D+-+2+%5Csqrt%7B3%7D++%7D++%3D+a+%2B+b+%5Csqrt%7B6%7D++%5C%5C++%5C%5C+on+%5C%3A+rationalizing+%5C%3A+the+%5C%3A+denominator+%5C%3A+we+%5C%3A+get+%5C%5C++%5C%5C++%3D++%5Cfrac%7B+%5Csqrt%7B2%7D+%2B++%5Csqrt%7B3%7D++%7D%7B3+%5Csqrt%7B2%7D++-+2+%5Csqrt%7B3%7D+%7D++%5Ctimes++%5Cfrac%7B3+%5Csqrt%7B2%7D++%2B+2+%5Csqrt%7B3%7D+%7D%7B3+%5Csqrt%7B2%7D++%2B+2+%5Csqrt%7B3%7D+%7D++%5C%5C++%5C%5C+using+%5C%3A+the+%5C%3A+identity+%5C%5C+%28a+%2B+b%29%28a+-+b%29+%3D++%7Ba%7D%5E%7B2%7D++-++%7Bb%7D%5E%7B2%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B+%5Csqrt%7B2%7D+%5Ctimes+3+%5Csqrt%7B2%7D++%2B++%5Csqrt%7B2%7D+++%5Ctimes+2+%5Csqrt%7B3%7D+%2B++%5Csqrt%7B3%7D+++%5Ctimes+3+%5Csqrt%7B2%7D++%2B++%5Csqrt%7B3%7D++%5Ctimes+2+%5Csqrt%7B3%7D+%7D%7B+%7B%283+%5Csqrt%7B2%7D%29+%7D%5E%7B2%7D++-++%7B%282+%5Csqrt%7B3%7D%29+%7D%5E%7B2%7D+%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B3+%5Ctimes+2+%2B+2+%5Csqrt%7B6%7D+%2B+3+%5Csqrt%7B6%7D+++%2B+2+%5Ctimes+3%7D%7B18+-+12%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B6+%2B+5+%5Csqrt%7B6%7D++%2B+6%7D%7B6%7D+++%5C%5C++%5C%5C+++%5Cfrac%7B12+%2B+5+%5Csqrt%7B6%7D+%7D%7B6%7D+%3D+a+%2B+b+%5Csqrt%7B6%7D+++%5C%5C++%5C%5C+++a+%3D++%5Cfrac%7B12%7D%7B6%7D++%5C%5C++%5C%5C+a+%3D+2+%5C%5C++%5C%5C+b+%3D++%5Cfrac%7B5%7D%7B6%7D++%5C%5C++%5C%5C+2%29+%5C%5C++%5Cfrac%7B5+%2B+2+%5Csqrt%7B3%7D+%7D%7B7+%2B+4+%5Csqrt%7B3%7D+%7D++%3D+a+%2B+b+%5Csqrt%7B3%7D++%5C%5C++%5C%5C+on+%5C%3A+rationalizing+%5C%3A+the+%5C%3A+denominator+%5C%3A+we+%5C%3A+get+%5C%5C++%5C%5C++%3D++%5Cfrac%7B5+%2B+2+%5Csqrt%7B3%7D+%7D%7B7+%2B+4+%5Csqrt%7B3%7D+%7D++%5Ctimes++%5Cfrac%7B7+-+4+%5Csqrt%7B3%7D+%7D%7B7+-+4+%5Csqrt%7B3%7D+%7D++%5C%5C++%5C%5C+using+%5C%3A+the+%5C%3A+identity+%5C%5C+%28a+%2B+b%29%28a+-+b%29+%3D++%7Ba%7D%5E%7B2%7D++-++%7Bb%7D%5E%7B2%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B5+%5Ctimes+7+-+5+%5Ctimes+4+%5Csqrt%7B3%7D+%2B+2+%5Csqrt%7B3%7D+++%5Ctimes+7+-+2+%5Csqrt%7B3%7D++%5Ctimes+4+%5Csqrt%7B3%7D+%7D%7B+%7B%287%29%7D%5E%7B2%7D+-++%7B%284+%5Csqrt%7B3%7D+%29%7D%5E%7B2%7D++%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B35+-+20+%5Csqrt%7B3%7D+%2B+14+%5Csqrt%7B3%7D+++-+8+%5Ctimes+3%7D%7B49+-+48%7D++%5C%5C++%5C%5C++%3D++35+-+24+-+20+%5Csqrt%7B3%7D+%2B+14+%5Csqrt%7B3%7D++%5C%5C++%5C%5C++11+-+6+%5Csqrt%7B3%7D++%3D+a+%2B+b+%5Csqrt%7B3%7D++%5C%5C++%5C%5C+a+%3D+11+%5C%5C++%5C%5C+b+%3D++-+6)
Hope this helps!!!!
Thanks....
☺☺
Here is the answer you were looking for:
Hope this helps!!!!
Thanks....
☺☺
Similar questions
English,
9 months ago
India Languages,
9 months ago
Math,
1 year ago
English,
1 year ago
Biology,
1 year ago